2012
DOI: 10.1210/en.2011-1665
|View full text |Cite
|
Sign up to set email alerts
|

Defining POMC Neurons Using Transgenic Reagents: Impact of Transient Pomc Expression in Diverse Immature Neuronal Populations

Abstract: Melanocortin signaling plays a central role in the regulation of phenotypes related to body weight and energy homeostasis. To specifically target and study the function of proopiomelanocortin (POMC) neurons, Pomc promoter elements have been utilized to generate reporter and Cre recombinase transgenic reagents. Across gestation, we find that Pomc is dynamically expressed in many sites in the developing mouse forebrain, midbrain, hindbrain, spinal cord, and retina. Although Pomc expression in most embryonic brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
87
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 56 publications
11
87
2
Order By: Relevance
“…It is important to note that endogenous Glp2r is not expressed in the brain regions where POMC-Cre is expressed highly transiently (40). Our data suggest that GLP-2R in Pomc-expressing progenitors is required for the control of feeding behavior and gastric emptying; yet it is unknown about the extent to which the Cremediated recombination in off-target sites (if any) may contribute to the observed metabolic phenotype.…”
Section: E862mentioning
confidence: 82%
See 1 more Smart Citation
“…It is important to note that endogenous Glp2r is not expressed in the brain regions where POMC-Cre is expressed highly transiently (40). Our data suggest that GLP-2R in Pomc-expressing progenitors is required for the control of feeding behavior and gastric emptying; yet it is unknown about the extent to which the Cremediated recombination in off-target sites (if any) may contribute to the observed metabolic phenotype.…”
Section: E862mentioning
confidence: 82%
“…It will be important to define if the 4th-ventricular GLP-2-mediated action is due to presynaptic effects of GLP-2R on axon terminals (arising from the ARC POMC neurons) and/or postsynaptic effects of GLP-2R on dendrites (of the NTS POMC neurons). We note that POMC-cre could be transiently expressed in embryonic non-POMC neurons in the brain (40), which might mediate recombination of GLP-2R in off-target cells. However, the POMC-Cre-mediated recombination of each floxed allele is unique, depending on endog- Fig.…”
Section: E861mentioning
confidence: 91%
“…However, Padilla et al 18 suggested that POMC is transiently expressed in several sites of the developing mouse brain and that this transient expression may be sufficient to cause recombination of floxed alleles in off-target neurons that could contribute to physiological phenotypes. However, the physiological significance of this transient expression of POMC in neurons has not, to our knowledge, been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…POMC is a precursor of a-MSH, which, when released from the axon terminals of POMC neurons, binds to and activates MC4R, thereby reducing food intake and body weight (Huszar et al 1997). In the adult rodent brain, the majority of POMC neurons are located in the hypothalamic arcuate nucleus (Cone 2005, Padilla et al 2012. Therefore, although we did not investigate POMC expression here in our micro-dissection of the arcuate nucleus, we assumed that our data for the whole hypothalamus approximately reflected Pomc mRNA levels in the arcuate nucleus.…”
Section: Discussionmentioning
confidence: 99%